A novel fluorescent carbon nanoparticles for detection of dipicolinic acid. Issue 11 (2nd November 2022) - Wang, Shuwei; Jiang, Xiangjian; Li, Ruiwei; Liu, Siyu
Abstract: In this work, we developed a simple route to synthesize green fluorescence carbon nanoparticles (FCPs) at room temperature with dopamine and p-phenylenediamine as raw materials. The FCPs exhibited a salient fluorescence emission peak at 525 nm and well stability in the intricate surroundings. Only Cu 2+ ions could significantly inhibited the fluorescence of FCPs and could be successfully detected in the concentration scope of 0–200 µmol·L −1 based on the fluorescence quenching of FCPs. The Cu 2+ ion-quenched fluorescence of FCPs system can be further recovered by the addition of dipicolinic acid (DPA) and could be utilized for DPA detection within the dynamic scope of 10–150 µmol·L −1 .